When English language matters: Internationalizing PhD research by Indonesian political scientists - Rüland, Jürgen (Englisia: Journal of Language, Education, and Humanities, 2023)
The essay traces frequent language problems and un(der)developed academic writing skills of Indonesian PhD students in the field of political science and international relations. The author thereby draws on personal experiences as a thesis supervisor. Apart from problematic scope conditions in the Indonesian university system, he identifies a lack of training in academic writing at the undergraduate and graduate levels of education and a missing research and publication culture in social sciences. The remainder of the essay reflects about how the problem of deficient language and academic writing skills can be remedied. It argues that both Indonesian universities and also host universities abroad must develop measures to overcome the identified problems.